STEM and gender gap: a systematic review in WoS, Scopus, and ERIC databases (2012–2022) - Beroíza-Valenzuela, Francisca; Salas-Guzmán, Natalia (Frontiers in Education, 2024)
The present article constitutes a comprehensive review of pertinent literature in the WoS, Scopus, and Eric databases (2012-2022), utilizing the PRISMA model (2020). A total of twenty-four articles were identified that focused on exploring the relationship between STEM education and the gender gap in the past decade, both at the national and international levels. The analysis is based on two key dimensions. The first dimension encompasses factors that contribute to the gender gap in STEM fields, while the second dimension comprises learning experiences designed to overcome biases, such as activities that enhance skills in science, mathematics, engineering, and technology, and foster a growth mindset. Based on the findings of this review, it can be inferred that research on gender and STEM primarily highlights principal issues using quantitative methodologies. The practical implications of this study include identifying key areas to address the gap and recognizing the need for quantitative research approaches. The study's limitations are evident in its focus on the binary gender gap between women and men, without considering other important factors. To future analyses, it is essential to incorporate the perspective of intersectionality.